Macrogenomics-based analysis of rumen microbial composition and their metabolic pathways in yaks under different dietary concentrate-to-forage ratios - Gou, Fajie; Han, Yincang; Sun, Yonggang; Ding, Weiqing; Jin, Shenwei; Liu, Yaqian; Chen, Jianyu (Frontiers in Microbiology, 2025)
This study aimed to investigate the regulatory mechanisms underlying feed efficiency (FE) in yaks by analyzing the composition of rumen microorganisms and their major metabolic pathways using metagenomic analysis under different dietary concentrate-to-forage ratios. A total of 40 Qinghai Plateau yaks (8–9 months old) with similar body weights (68.725 ± 18.973 kg) were randomly assigned to four treatment groups (n = 10per group). The experimental groups were fed diets with concentrate-to-forage ratios of 80:20 (C80), 65:35 (C65), 50:50 (C50), and 35:65 (C35), respectively. The study included a 15-day pre-feeding period followed by a 105-day experimental feeding period. The results indicated that the total weight gain in the C65 group was significantly higher than in the C50 and C35 groups by 29.91 and 28.97%, respectively (p < 0.05). Additionally, the rumen pH in the C80 group was significantly higher than in the C65, C50, and C35 groups (p < 0.05). Metagenomic analysis revealed significant differences (p < 0.05) in bacterial and archaeal community compositions across groups. Bacteroidota, Bacillota, Prevotella, Bacteroides, and Ruminococcus were identified as the dominant bacterial taxa at the phylum and genus levels. Functional analysis of rumen microbial metabolism showed that in the C35 group, pathways related to starch and sucrose metabolism, as well as fructose and mannose metabolism, were significantly different from those in other groups. The C35 group exhibited higher activity in functional pathways related to starch and sucrose metabolism, fructose and mannose metabolism, cellulose degradation, and methanolysis. In contrast, the C80 group showed greater activity in cellulose degradation and methane metabolism. Notably, the C65 group exhibited the highest activity in sugar metabolism pathways (ko00500), facilitating starch and soluble sugar degradation and the rapid conversion of pyruvic acid into acetic acid and propionate. This enhanced energy utilization efficiency, suggesting a superior capacity for sugar metabolism. In conclusion, the dietary composition of the C65 group demonstrated the most favorable effects on growth performance, rumen fermentation optimization, and microbial balance maintenance.